First‐line treatment of stage IIB to stage IV classical Hodgkin lymphoma in Italy, Israel, and Spain: Patient characteristics, treatment patterns, and clinical outcomes. Issue 2 (19th April 2022) - Avigdor, Abraham; Trinchese, Fabrizio; Gavini, Francois; Bent‐Ennakhil, Nawal; Dalal, Mehul; Zomas, Athanasios; Gettner Broun, Sharmeen; Gini, Guido
Abstract: Classical Hodgkin lymphoma (cHL) is curable in 90% of cases, but advanced stage patients who do not respond well to first‐line (1L) therapy have poorer outcomes. This retrospective study examines patient characteristics, treatment patterns, clinical outcomes, and safety management of 1L cHL therapies in common clinical practice in Italy (IT), Israel (IL), and Spain (SP). The overall sample ( n  = 256) included patients with stage IIb to IV cHL, of which 86.3% received ABVD as 1L therapy ( n  = 221). Clinical outcomes were similar for the overall population and ABVD subsample: complete response (CR) in 75% and 76.5%; 30‐month (30‐mo) survival (OS) of 92.5% and 93.6%; and 30‐mo progression‐free survival (PFS) of 70.7% and 72.6%. Thirty‐month PFS was significantly lower for patients ≥ 60 years and/or with high (4–7) IPS. Treatment‐induced pulmonary and cardiac toxicities, and febrile neutropenia occurred, respectively, in 10%, 2.3%, and 6.8% of ABVD‐treated patients. Interim PET or PET‐CT scans were performed after two cycles of 1L therapy (PET2) for 70.3% and 66.6% of the overall and ABVD cohorts, respectively. PET2 positive rates were nearly 30% (49/173), yet PET‐adapted strategy of dose modification only occurred in a small fraction of patients.